Impact of Probiotic Bacteria on Respiratory Allergy Disorders - Jakubczyk, Dominika; Górska, Sabina (Frontiers in Microbiology, 2021)
Respiratory allergy is a common disease with an increased prevalence worldwide. The effective remedy is still unknown, and a new therapeutic approach is highly desirable. The review elaborates the influence of probiotic bacteria on respiratory allergy prevention and treatment with particular emphasis on the impact of the current methods of their administration – oral and intranasal. The background of the respiratory allergy in complex thus, we focused on the usefulness of probiotics in the alleviation of different allergy factors, in particular involved in pathomechanism, local hypersensitive evidence and the importance of epithelial barrier. In this review, we have shown that 1) probiotic strains may vary in modulatory potential in respiratory allergy, 2) probiotic bacteria are beneficial in oral and intranasal administration, 3) recombinant probiotic bacteria can modulate the course of respiratory allergy.